THE MORPHO-PHONEMIC PROCESSES IN INDONESIAN ADVERTISEMENT’S SLOGANS - Octavia Chandra Dewi; Lia Maulia Indrayani; Ypsi Soeria Soemantri (University of Muhammadiyah Malang, 2020)
The use of slogans in the advertisements to introduce and to attract public’s attention upon the products advertised are essential. The use of morpho-phonemic forms as the morphological process in the Indonesian advertisements’ slogans nowadays are interesting to be analyzed since there are lots of them use unique forms to attract public’s attention upon the product. The public’s attention upon the advertisements would influence the level of public’s awareness upon the product and eventually would raise the number of purchase and the usage of the product offered. This research explained the forms of the morphological process used in the Indonesian advertisement’s slogans, and the purposes of the morphological process used in the Indonesian advertisement’s slogans. Based on O'Grady and Dobrovolsky’s theories, this research uses descriptive qualitative method by observing and documenting the forms of morpho-phonemic changing which are used in Indonesian slogans, continued by analyzing the data. The objects of the study were the texts in advertisement’s slogans. The sources of the data were the Indonesian advertisement’s slogans from various types of product, which were aired or published in Indonesia. The forms of the morpho-phonemic changing were studied based on morphological processes in morphology. Slogans should attract the attention from public upon the product advertised to consume or to use it. It is hope that these findings will be useful for the development of language use especially in advertising.